Verdier i konflikt Etikk i et mangfoldig samfunn - Lysaker, Odin; Fredwall, Terje Emil (Cappelen Damm Akademisk/NOASP (Nordic Open Access Scholarly Publishing), 2020)
"We live in a diverse society characterized by different and to some extent contradictory values. Sometimes they create community. Other times they generate value conflicts. In this book, twelve Norwegian researchers write about such value conflicts and the way they occur in working life and the public sphere. Common to many of the contributions of this book is the attempt to highlight so-called value-based community of disagreement. This means that we agree to disagree. As a society, citizens can try to gather around some shared, fundamental values, but we cannot demand that all the members of the society agree on personal values. "